MENULIS TEKS EKSPLANASI MENGGUNAKAN METODE PICTURE AND PICTURE PADA SISWA KELAS VII SMP - Baiq Emilia Susdiana (Center of Language and Cultural Studies, 2017)
This study aims to describe process and achievement of expository writing skills through the Picture and Picture teaching method. This study used classroom action research design assigning 31 students in the seventh graders of SMP ISLAM Az-zikra Tastura Lombok in 2016/1017. The study was conducted in two cycles each of which was staged using planning, implementation, observation, and reflection. The results of data analysis showed: (1) attainment in writing expository writing after picture and picture model was incurred in cycle 1 and cycle 2 increased from 76% into 89%; (2) the learning process showed that in cycle 1, students were successful to understand text structure of expository writing; and in cycle 2 students accomplished minimum standard of mastery. During the learning process: initial, core, concluding stages, students enthusiastically followed each stage of learning at their own interests and struggles.